2012
DOI: 10.1186/1472-6831-12-22
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for infection in oral cancer patients undergoing different treatments protocols

Abstract: BackgroundOver the past decade, advances in cancer treatments have been counterbalanced by a rising number of immunosuppressed patients with a multitude of new risk factors for infection. Hence, the aim of this study was to determine risk factors, infectious pathogens in blood and oral cavity of oral cancer patients undergoing different treatment procedures.MethodsThe present prospective cohort analysis was conducted on the patients undergoing treatment in the radiotherapy unit of Regional Cancer Institute, Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 60 publications
3
51
1
15
Order By: Relevance
“…Overall, C. albicans fungi seemed to be the most significant oral cavity pathogen in radiotherapy. Gram negatives such as P. aeruginosa and K. pneumoniae were observed as main pathogens isolated from the blood of radiotherapy‐treated patients (Panghal et al , ).…”
Section: Microbiota and Their Impact On Oral Mucositismentioning
confidence: 99%
“…Overall, C. albicans fungi seemed to be the most significant oral cavity pathogen in radiotherapy. Gram negatives such as P. aeruginosa and K. pneumoniae were observed as main pathogens isolated from the blood of radiotherapy‐treated patients (Panghal et al , ).…”
Section: Microbiota and Their Impact On Oral Mucositismentioning
confidence: 99%
“…Some authors [140] have observed that gram-positive bacteria prevail over the gram-negative ones as infectious pathogen in developed countries, probably because of the routine use of prophylactic oral antibiotics (such as quinolones, which can also favor bacteriaceae) [141] and the use of CVC [140]. Conversely gram-negative prevails in developing countries [142].…”
Section: -The Evaluation Of the Suspected Infection Sourcementioning
confidence: 99%
“…As pathogens can play an important role in mucositis, we also included Streptococcus pyogenes, Pseudomonas aeruginosa and Klebsiella oxytoca. S. pyogenes is a common oral pathogen (Wescombe et al, 2012), whereas P. aeruginosa and Klebsiella were recorded in the oral cavity of chemotherapy-treated patients (Panghal et al, 2012). Furthermore, oral mucositis has been associated with an increase in Klebsiella (Marsh & Martin, 1999).…”
Section: Introductionmentioning
confidence: 99%